Histopathological pattern of cutaneous disorders in tertiary care center in Shahjahanpur district of India - Singh, Amar; Pant, Astha (International Journal of Research in Medical Sciences, 2020)
Background: Histopathological examination is most commonly needed and used investigation in dermatology. The main objective of this study is to share our experience with skin lesions from a tertiary health Centre by describing the histopathological patterns of 675 consecutive cases. Methods: The study was retrospective and was conducted in those patients who attended the OPD. A total of 675 cases were sent for histopathological examination. Further they were classified into various histological categories based on the site and pattern of involvement. Inclusion criteria involves all skin biopsies sent for histopathology examination, exclusion criteria was none. Results: Most common histopathological entity was infectious disease with 22.52% cases leading in this study. Out of which Hansen disease is on top with 16.29% which was followed by cutaneous tuberculosis with 3.70% (25) cases. Second most common group was of psoriasiform reactions with 9.77% cases. In this group most common disorder was psoriasis vulgaris with 5.92% (40) cases. Third and fourth most common group were spongiotic dermatitis and lichenoid dermatitis which presented with 9.18% and 9.03% cases with a minimal difference of 1 case. Conclusions: A huge diversity in skin lesions was noticed in our study ranging from nonspecific dermatitis to malignant melanoma conditions. There was a younger age predominance regarding the patient presentation. Hansen’s disease still remains a single entity in India for which skin biopsy are required.